Enrochements et regard sur l’aqueduc de la Brévenne à Dardilly, chemin du Combert (Métropole de Lyon) - Sylvain Motte; Cécile Ramponi (Gallia)
Two archaeological operations, 50 m apart, conducted at Dardilly (France), provided new data on the a Brévenne aqueduct with the discovery of two sizeable platforms of large slabs, one of them combined with a manhole. These two facilities are located at the elbows of the aqueduct. At Combert Sud, the paved platform is located on an old talweg perpendicular to the structure and is combined with a manhole. At Combert Nord, information remains limited, but the structure is identical.These developments were probably intended to support the ground around the aqueduct and protect it from run-off from the slopes. The Combert Sud platform also facilitated access to the manhole at the southern end of the paved platform.